Are Pakistani construction professionals truly happy? A benchmarking approach - Hamna Bukhari (Elsevier, 2021)
Construction organizations are challenged with effective management of their human resource (HR) as both are integral to each other. But the state of practice in the developing countries is not encouraging and construction professionals found themselves less motivated and enthusiastic about their job. This pushes to study the motivational needs of construction professionals of different career levels. Therefore, the current study benchmarks the HR practices of the construction industry of Pakistan to measure if there is any difference between what professionals truly value and what they get. In doing so, data was collected from 250 professionals through a questionnaire survey. Results reveal that most of the motivational needs are not gratified and the only stakeholder doing better are clients who’s mid- and end-career professionals feel somewhat satisfied. Practical suggestions are provided to help the construction industry upgrade its HR vision and facilitate its most precious resource.